Analysis Of Factors Influencing Green Economic Growth In Dumai City - Dylan Haikal Arigi; Yelly Zamaya (UNIVED Press, 2025)
Growth economy green can achieved with utilise potential that exists in various sector as in the sector agriculture , forestry and fisheries . However For reach growth sustainable economy , is needed understanding deep to factors that influence it. Research This aiming For know influence foreign investment, domestic investment and exports​​ Good in a way partial and also simultaneous to growth economy green in Dumai City. Population in study This is report data statistics sector agriculture , forestry and fisheries of Dumai City in the period 2009-2023, with amount sample as many as 15 data. The analysis model used is analysis multiple linear regression , which is processed with SPSS software assistance . Research results show that foreign investment and domestic investment​​​​ partial No influential significant to growth economy green in Dumai City . While export influential positive and significant to growth economy green in Dumai City . Foreign investment , domestic investment and exports​ in a way together influential positive and significant to growth economy green in Dumai City.